2019
DOI: 10.5664/jcsm.7806
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Desaturations Reflects OSA-Related Daytime Sleepiness Better Than AHI

Abstract: Study Objectives: The aim was to investigate how the severity of apneas, hypopneas, and related desaturations is associated with obstructive sleep apnea (OSA)-related daytime sleepiness. Methods: Multiple Sleep Latency Tests and polysomnographic recordings of 362 patients with OSA were retrospectively analyzed and novel diagnostic parameters (eg, obstruction severity and desaturation severity), incorporating severity of apneas, hypopneas, and desaturations, were computed. Conventional statistical analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 23 publications
9
67
0
Order By: Relevance
“…AHI, ODI and AI) are not. This finding is supported by our previous study [7], showing that OSA-related objective daytime sleepiness is more strongly associated with the severity of individual desaturations than the number of apneas and hypopneas. Furthermore, these results correspond with previous studies [8,9,[18][19][20][21][22], by showing that conventional AHI-based assessments of OSA have little connection to poor PVT performance.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…AHI, ODI and AI) are not. This finding is supported by our previous study [7], showing that OSA-related objective daytime sleepiness is more strongly associated with the severity of individual desaturations than the number of apneas and hypopneas. Furthermore, these results correspond with previous studies [8,9,[18][19][20][21][22], by showing that conventional AHI-based assessments of OSA have little connection to poor PVT performance.…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings have also been reported in other studies investigating cognitive impairment in OSA patients and healthy individuals[9,19,20,22,35]. Moreover, in our recent studies, we reported that a larger desaturation area is a significant predictor of objective daytime sleepiness and the most detrimental health consequences of OSA[7,29,31]. Together with these findings, this study highlights the urgent need to develop the diagnostics of OSA beyond the AHI.…”
supporting
confidence: 91%
See 3 more Smart Citations